(untitled) (Global Journal of Management and Business Research, 2021)
Out of the source characteristics, the study discovers the impact of social media marketing towards purchase intention among generation Y and Z referring to fast food franchises in the Colombo district. Although there were many studies conducted in other countries on the impact of social media marketing towards purchase intention, there is a deficiency of literature in the Sri Lankan context regarding the same area. Furthermore, this study explores how the purchase intention differs from one generation to another. The study focuses on generation Y and Z. Franchise fast food industry in Sri Lanka is using social media marketing widely for marketing activities compared to other industries.